Out of the trap: Conversion funnel business model, customer switching costs, and industry profitability - ABOLFATHI, Niloofar (Institutional Knowledge at Singapore Management University, 2022)
Research Summary: Across many industries, firms employ a conversion funnel business model to attract customers with basic and affordable products, generate lock-in, and then sell them more advanced and expensive products. We argue that this business model, coupled with high customer switching costs, results in a market outcome characterized by aggressive pricing and reduced profits. A sudden reduction in customer switching costs disrupts the conversion funnel and can eventually increase industrywide prices and profitability, an outcome that contradicts conventional wisdom in strategy research. We develop a stylized model to formalize our ideas and provide supportive evidence using a difference-in-differences methodology with staggered treatment for a large, global sample of mobile telecommunications operators.Managerial Summary: Industry changes that lower customer frictions can surprisingly be beneficial for companies. Building on the telecommunications industry, we document how a reduction in customer switching costs following mobile number portability increases the profitability of mobile operators. We explain this finding based on a change in companies' business model. When switching costs are high, companies adopt a funnel business model designed to convert customers from basic to advanced products. While advantageous for a single company, when strategic interactions are accounted for, the diffusion of this business model has a depressive effect on average market prices and profitability. A reduction in customer switching costs breaks the funnel and decouples product pricing decisions that, counterintuitively, can lead to higher industrywide prices and greater profitability.